2010
DOI: 10.1002/bit.22645
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐permeable membrane retention of synovial fluid lubricants hyaluronan and proteoglycan 4 for a biomimetic bioreactor

Abstract: Synovial fluid (SF) contains lubricant macromolecules, hyaluronan (HA), and proteoglycan 4 (PRG4). The synovium not only contributes lubricants to SF through secretion by synoviocyte lining cells, but also concentrates lubricants in SF due to its semi-permeable nature. A membrane that recapitulates these synovium functions may be useful in a bioreactor system for generating a bioengineered fluid (BF) similar to native SF. The objectives were to analyze expanded polytetrafluoroethylene membranes with pore sizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Previous research on the effect of human FLS cells has shown that inflammatory cytokines increase cell proliferation, perhaps explaining the thickening of the synovial capsule observed in OA-associated synovitis 23; 40; 41 . The previously observed proliferative stimulus provided by these pro-inflammatory cytokines may have inhibited by the presence of growth factors in FBS used to supplement the culture media in the present study 42; 43 . Cytokine stimulated FLS have been shown to produce a number of inflammatory factors involved in OA and RA, including IL-6, IL-8, NO, and PGE2 23; 40; 41; 44 that can lead to matrix degradation, as observed here.…”
Section: Discussionmentioning
confidence: 49%
“…Previous research on the effect of human FLS cells has shown that inflammatory cytokines increase cell proliferation, perhaps explaining the thickening of the synovial capsule observed in OA-associated synovitis 23; 40; 41 . The previously observed proliferative stimulus provided by these pro-inflammatory cytokines may have inhibited by the presence of growth factors in FBS used to supplement the culture media in the present study 42; 43 . Cytokine stimulated FLS have been shown to produce a number of inflammatory factors involved in OA and RA, including IL-6, IL-8, NO, and PGE2 23; 40; 41; 44 that can lead to matrix degradation, as observed here.…”
Section: Discussionmentioning
confidence: 49%
“…4f). This observation has important ramifications for engineering cartilage constructs with lubricious properties (Blewis et al, 2010). Surprisingly, the hydrodynamic stimulation‐induced secretion of PRG4 was not restricted to the superficial layer, but was observed deeper within the TEC hydrogels.…”
Section: Discussionmentioning
confidence: 99%
“…It is comprised of fibroblast-like synoviocytes (FLS), which produce the lubricating molecules hyaluronan and lubricin, embedded within an extracellular matrix composed of hyaluronan, collagen and proteoglycans that acts as a semi-permeable membrane to mediate solute transport (Blewis, Lao et al 2010, Hui, McCarty et al 2012). FLS reside in the intimal layer of this membrane and are thus directly exposed to shear stresses induced in a thin layer of synovial fluid by the relative movement between the synovium and cartilage surfaces during joint articulation (Rattner, Sciore et al 2010).…”
Section: Introductionmentioning
confidence: 99%